Characterization of a Hormone-Responsive Organotypic Human Vaginal Tissue Model: Morphologic and Immunologic Effects. (August 2015) - Ayehunie, Seyoum; Islam, Ayesha; Cannon, Chris; Landry, Timothy; Pudney, Jeffrey; Klausner, Mitchell; Anderson, Deborah J.
Estrogen and progesterone regulate proliferation and differentiation of epithelial cells in the female genital tract. We investigated the effects of these hormones on reconstructed human organotypic vaginal epithelial tissue models (EpiVaginal). We ascertained that epithelial cells in the tissue models express estrogen and progesterone receptors. Treatment with estradiol-17β (E2 ) significantly increased epithelium thickness and transepithelial electrical resistance (TEER), whereas progesterone (P) treatment resulted in thinning of the epithelium and decreased TEER when compared with untreated controls. Exposure to E2 increased (1) the expression of the progesterone receptor B (PR-B), (2) accumulation of glycogen in suprabasal cells, (3) epithelial differentiation, and (4) the expression of a number of gene pathways associated with innate immunity, epithelial differentiation, wound healing, and antiviral responses. These findings indicate that EpiVaginal tissues are hormone responsive and can be used to study the role of female reproductive hormones in innate immune responses, microbial infection, and drug delivery in the vaginal mucosa.